Socialization of The Potential Revenue of Local Taxes for The Younger Generation of Water and Swamp Areas - Rahmawati, Rini; Juniar, Asrid; Wardhana, Ali; Hamdani, Hamdani; Wijaya, Melinda; Fitriani, Lisa Nor; Tiofajrian, Muhammad Rosyad (Pascasarjana Universitas Mataram, 2024)
Regional taxes as a source of original regional income are one of the basic capital for regional governments to obtain funds for development and to fulfill regional expenditures thereby reducing dependence on the central government and its subsidies. The problem that prospective taxpayers often experience is a lack of knowledge about taxes. Limitations in access to adequate information about taxes, such as seminars, guides, or assistance from tax experts, can lead to inaccurate perceptions of taxes. This condition results in a decrease in the level of compliance with paying taxes, which will ultimately be detrimental to the government in financing public services and infrastructure development needed for community welfare. People who live in areas dominated by water and swamp areas must be aware that there are unique features that have different potential for Regional Original Income (PAD). This activity aims to increase local taxpayer compliance among the younger generation through the activity of Equating Perceptions of Potential Regional Tax Revenue from Water and Swamp Areas for the Young Generation at the El Qudwah Foundation in the Barito Kuala district. The results show that socialization regarding taxes is really needed by the younger generation so that they are obedient in paying taxes, increasing tax compliance will have an impact on increasing local original income, which is very beneficial for regional development whose aim is to improve the welfare of regional communities both in water and swamp areas. in all city districts in South Kalimantan province.